Straightening the crooked: intraspecific divergence of stem posture control and associated trade-offs in a model conifer. (5th December 2021) - Sierra-de-Grado, Rosario; Pando, Valentin; Voltas, Jordi; Zas, Rafael; Majada, Juan; Climent, Jose
Abstract: Although the straightening capacity of the stem is key for light capture and mechanical stability in forest trees, little is known about its adaptive implications. Assuming that stem straightening is costly, trade-offs are expected with competing processes such as growth, maintenance, and defence. We established a manipulative experiment in a common garden of Pinus pinaster including provenances typically showing either straight-stemmed or crooked-stemmed phenotypes. We imposed a bending up to 35º on plants aged 9 years of both provenance groups and followed the straightening kinetics and shoot elongation after releasing. Eight months later, we destructively assessed biomass partitioning, reaction wood, wood microdensity, xylem reserve carbohydrates, and phloem secondary metabolites. The experimental bending and release caused significant, complex changes with a marked difference between straight- and crooked-type plants. The straight-type recovered verticality faster and to a higher degree and developed more compression wood, while displaying a transitory delay in shoot elongation, reducing resource allocation to defence and maintaining the levels of non-structural carbohydrates compared with the crooked type. This combination of responses indicates the existence of intraspecific divergence in the reaction to mechanical stresses that may be related to different adaptive phenotypic plasticity. Abstract : Bending triggered contrasting responses between straight- and crooked-stemmed provenances of maritime pine linked to the straightening process, showing different trade-offs with other features related to growth, maintenance, and defence.